A framework for the implementation of computer based testing for Saudi Arabia secondary schools [electronic resource] - Hakami, Yahya Abduh A., 1981- author; Ab. Razak Che Hussin (2014)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2014